'When there's blood involved, a line been crossed': Spike/Eric slash and the fascinations of the crossover text. Issue 2 (1st October 2017) - Jones, Bethan
Buffy the Vampire Slayer (1997–2003) and True Blood (2008–14) are arguably two of the most popular vampire television series. Given the many similarities between them this is, perhaps, not surprising: both focus on a female character who falls in love with a vampire; both draw on the notion of the Byronic hero; and both feature a blonde bad boy who quickly became a fan favourite. Indeed, an August 2016 search on Fanfiction.net for stories featuring Spike yields 10, 476 hits, while Eric appears in 2, 923 works (Angel features in 6153 and Bill in 708). Henry Jenkins suggests that fanfiction is born from a combination of both fascination and frustration: if fans were not fascinated with a series they would not continue the storyworld, but if they were not frustrated with aspects of it they would find nothing to write about. In this article I argue that fascination with a text occurs across multiple storyworlds and that the crossover text is one way in which fans make this fascination transparent. I further argue that while much work on slash fiction exists, it has primarily focused on pairings from within the same narrative: Harry/Draco; Sherlock/John; Mulder/Krycek and analysing slash featuring characters from across storyworlds offers us a fruitful understanding of fans' intertextual knowledge and the way in which this knowledge is applied in fanworks. Furthermore, I contend that the crossover slash story complicates current academic discourse around slash and ask how we might begin to theorize the slash crossover both in relation to existing slash fic and representations and rewritings of gender.